Intractable Temporal Lobe Epilepsy (TLE) From Tuberculoma; Microneurosurgical Management of by Amygdalohippocampectomy with Lesionectomy Plus Standard Anterior Temporal lobectomy: A Case Report and Short Review of Literature (Journal of Surgical Sciences, 2019)
Patient presenting as a case of Temporal Lobe Epilepsy (TLE) are usually resistant to antiepileptic drugs and surgery is the treatment of choice. This type of epilepsy may be due to Mesial Temporal Sclerosis (MTS), tumors [i.e. low grade glioma, Arterio-venous Malformation (AVM) etc], trauma, infection (Tuberculosis) etc. Here we report a case of surgically treated TLE that was due to a large tuberculoma in medial temporal lobe. Intractable epilepsy caused by tuberculoma is rare. The only presenting symptoms was Complex partial seizure (Psychomotor epilepsy) for which the patient underwent scalp EEG (Electro Encephalography) and MRI (Magnetic resonance imaging) of brain. The patient was managed by amygdalohippocampectomy with lesionectomy plus standard anterior lobectomy. Postoperatively she was on anti-tubercular therapy and on carbamazepine. The case was seizure and disease free till last follow up.Journal of Surgical Sciences (2012) Vol. 16 (2) : 106-109